POPULASI BAKTERI PENAMBAT NITROGEN DAN KARAKTERISTIK TANAH PADA RHIZOSFER TANAMAN PAKAN LEGUMINOSA DAN RUMPUT DI LAHAN KERING PADA MUSIM HUJAN - Wulandari F; S. A. Lindawati; N. G. K. Roni (Udayana University, 2019)
Forage as the main feed for ruminants needs to be considered for availability throughout the year. Factors that influence the availability of forage for feed throughout the year are the influence of the season, the condition of the land, and the presence of soil microorganism. One of the important soil microorganism is nitrogen fixing bacteria (N). This study aimed to determine the population of nitrogen fixing bacteria and soil characteristics in the rhizosphere of legumes and grass at dry land in rainy season. The study was conducted at the Research Station of the Faculty of Animal Husbandry, Udayana University, Pengotan Village, Bangli Regency, followed by a sample analysis at the Animal Production and Microbiology Technology Laboratory, Faculty of Animal Husbandry and the Laboratory of Soil Science, Faculty of Agriculture, Udayana University for 3 months. The design used was a completely randomized design consisting of 5 treatments and 4 replications. The five treatments were non rhizosphere (NR), Gliricidia sepium rhizosphere (RG), Stylosanthes guianensis rhizosphere (RS), Brachiaria decumbens rhizosphere (RB), and Pennisetum purpureum rhizosphere (RP). The variables observed in this study are the population of N-fixing bacteria, N elements, soil acidity (pH), soil temperature, and soil texture. The data obtained from this study were analyzed using annova, if there were significant differences (P<0.05) the analysis was continued by Duncan’s multiple range test. The results showed that the population of N-fixing bacteria, N elements, and soil texture were not significantly different, while the acidity (pH) and soil temperature were significantly different influenced by the rhizosphere of the plant. Based on the results of the study it can be concluded that the population of N fixing bacteria, N elements, and soil texture was not affected by the rhizosphere of the plant, the acidity (pH) of the soil decreases in all rhizosphere of plants, while the soil of temperature increases in Gliricidia sepium and Pennisetum purpureum rhizosphere. Key words: nitrogen fixing bacteria, soil characteristics, rhizosphere